A MODERN APPROACH TO PHYSICAL EDUCATION CLASSES IN GENERAL SECONDARY SCHOOLS - Murodjonov F. (Galaxy International Interdisciplinary Research Journal, 2023)
The article is about the Physical culture, and sports is an integral part of the educational process. Also,the new model of modern educational technologies.